A Lineage-Specific Paralog of Oma1 Evolved into a Gene Family from Which a Suppressor of Male Sterility-Inducing Mitochondria Emerged in Plants. (27th August 2020) - Arakawa, Takumi; Kagami, Hiroyo; Katsuyama, Takaya; Kitazaki, Kazuyoshi; Kubo, Tomohiko
Abstract: Cytoplasmic male sterility (MS) in plants is caused by MS-inducing mitochondria, which have emerged frequently during plant evolution. Nuclear restorer-of-fertility ( Rf )genes can suppress their cognate MS-inducing mitochondria. Whereas many Rf s encode a class of RNA-binding protein, the sugar beet (Caryophyllales) Rf encodes a protein resembling Oma1, which is involved in the quality control of mitochondria. In this study, we investigated the molecular evolution of Oma1 homologs in plants. We analyzed 37 plant genomes and concluded that a single copy is the ancestral state in Caryophyllales. Among the sugar beet Oma1 homologs, the orthologous copy is located in a syntenic region that is preserved in Arabidopsis thaliana . The sugar beet Rf is a complex locus consisting of a small Oma1 homolog family ( RF-Oma1 family) unique to sugar beet. The gene arrangement in the vicinity of the locus is seen in some but not all Caryophyllalean plants and is absent from Ar. thaliana . This suggests a segmental duplication rather than a whole-genome duplication as the mechanism of RF-Oma1 evolution. Of thirty-seven positively selected codons in RF-Oma1,  twenty-six of these sites are located in predicted transmembrane helices. Phylogenetic network analysis indicated that homologous recombination among the RF-Oma1 members played an important role to generate protein activity related to suppression. Together, our data illustrate how an evolutionarily young Rf has emerged from a lineage-specific paralog. Interestingly, several evolutionary features are shared with the RNA-binding protein type Rf s. Hence, the evolution of the sugar beet Rf is representative of Rf evolution in general.